Genetic algorithms for swarm parameter tuning - Chee, Glenn Jun Yuan (2019)
Swarming behaviour is based on the aggregation of simple drones exhibiting basic instinctive reactions to stimuli. However, to achieve overall balanced/interesting behaviours, the relative importance of these instincts as well their internal parameters must be tuned. This project attempts to achieve a series of non-trivial swarm-level behaviours by applying Genetic Programming as means of such tuning.